Thingspeak Cloud Server Based IoT Equipped Firefighting Robot - Nadakuditi Gouthamkumar; Venakteshwarlu S.; B Sharath Kumar; Pulluri Harish; Preeti; Goud B. Srikanth (E3S Web of Conferences, 2025)
This paper presents the development of a novel firefighting robot prototype designed to mitigate fire incidents while enhancing situational awareness through modern technological integration. The robot employs an array of sensors, including IR sensors for flame detection, MQ-2 gas sensors for hazardous gas monitoring, and LM-35 temperature sensors for thermal assessment, all orchestrated by microcontrollers like Arduino Uno and ESP-12E. A key innovation lies in the real-time transmission of environmental data to a cloud server, enabling remote monitoring and analysis. Furthermore, the prototype is equipped with user-friendly control via Wi-Fi connectivity through the Blynk App on Android devices, providing intuitive operational functionality. The results demonstrate the prototype’s efficacy in detecting fires, collecting and transmitting critical data, and facilitating effective fire suppression measures, offering a significant step forward in fire safety automation.